2010
DOI: 10.1007/s11356-010-0417-9
|View full text |Cite
|
Sign up to set email alerts
|

Hexachlorocyclohexane (HCH) as new Stockholm Convention POPs—a global perspective on the management of Lindane and its waste isomers

Abstract: It can be expected that most locations where HCH waste was discarded/stockpiled are not secured and that critical environmental impacts are resulting from leaching and volatilization. As parties to the Stockholm Convention are legally required to take action to stop further POPs pollution, identification and evaluation of such sites are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
177
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 392 publications
(198 citation statements)
references
References 24 publications
0
177
0
5
Order By: Relevance
“…Once released to the environment, HCH partitions into the air, water, sediments and soil, and accumulates in biota. Technical HCH is no longer used as an insecticide in most parts of the world, but its isomers are still reported to occur in surface waters, sediments, soil and biota in countries where it has long been banned because of its persistence in the environment (Zhao et al, 2009;Hu et al, 2010;Vijgen et al, 2011). Among banned organochlorines, Brun et al (2008) reported α-and γ-HCH among the most frequently detected chemical substances in wetprecipitation across Atlantic Canada.…”
Section: Persistencementioning
confidence: 99%
See 2 more Smart Citations
“…Once released to the environment, HCH partitions into the air, water, sediments and soil, and accumulates in biota. Technical HCH is no longer used as an insecticide in most parts of the world, but its isomers are still reported to occur in surface waters, sediments, soil and biota in countries where it has long been banned because of its persistence in the environment (Zhao et al, 2009;Hu et al, 2010;Vijgen et al, 2011). Among banned organochlorines, Brun et al (2008) reported α-and γ-HCH among the most frequently detected chemical substances in wetprecipitation across Atlantic Canada.…”
Section: Persistencementioning
confidence: 99%
“…Technical HCH is a mixture of five isomers: α (alpha)-HCH (55-80%), β (beta)-HCH (5-14%), γ (gamma)-HCH (8-15%), δ (delta)-HCH (2-16%) and ε (epsilon)-HCH (3-5%) (Vijgen et al, 2011). The proportion of the different isomers in technical products varied due to differences in production processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little attention has been paid to the combined impact of wind system and temperature on the atmospheric outflow of legacy POPs from Asia/China. α-hexachlorocyclohexane (HCH), listed recently as a new POP by Stockholm Convention, 13 is the most representative isomer of technical HCH. China was the largest user of technical HCH in the world.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Core IHPA themes (www.ihpa.info) addressed in this issue include the management of pesticide/POPs stockpiles (Van Thuong et al 2014;Pieterse et al 2015;Vijgen et al 2011); pollution by HCH and other POPs at former production site (Amirova and Weber 2015; Torres et al 2013;Wimmerová et al 2015;Wycisk et al 2013); and actions and proposals for moving towards solutions for legacy POPs contamination .…”
mentioning
confidence: 99%